Membangun Kepedulian Masyarakat Terhadap Problem Sampah Melalui Laboratorium Sampah di Marengan Laok Kalianget Sumenep - Firdausi Firdausi; Moh Khairul Jazil Al-Faizi; Nurul Luthfi Asyiqullah (TAAWUN, 2024)
Population growth in Indonesia is increasing rapidly; of course, the volume of waste is growing because people's activities continue using things that are not environmentally friendly. This phenomenon can be seen in Marengan Laok Village, Kalianget District, Sumenep Regency, which is claimed to be a slum village. The community service carries two goals: building awareness and providing real action to residents by providing theoretical and practical knowledge to the community about waste processing or recycling to solve this problem. In this case, the service uses a Participatory Action Research (PAR) approach, which addresses issues and fulfills the practical needs of society, the production of knowledge, and the process of social change, as well as raising collective critical awareness. After analysis, the community's indifference is based on a lack of knowledge, skills in recycling domestic waste, and a lack of attention from the government. Through a united, socialist community culture and support from the village government and local community leaders, the PCM program, which consists of preventing, controlling, and recycling waste, can gradually make people aware of the importance of protecting the environment. This success is supported by the establishment of the UPT Abhinar Waste Laboratory, which is used as extra handling so that domestic waste does not endanger people's lives and residents can recycle organic and inorganic waste, such as making eco paving blocks, accessories, bags, and others.